(untitled) (Педагогіка вищої та середньої школи, 2009)
Basing on theories of outstanding philosophers, educators and psychologists the author makes an attempt to outline some ways of spirinally-moral revival of a student’s personality taking into account the realia of today - the crisis of spirituality of the society.